Penerimaan dan Kualitas Hidup Caregiver dengan Kekambuhan pada Pasien Rawat Jalan Skizofrenia - Medina Hayati; Rin Widya Agustin; Rahmah Saniatuzzulfa (Philanthropy: Journal of Psychology, 2021)
Abstract. Relapse is a state of recurrence and worsening symptom experienced by patient. Acceptance and quality of life of caregivers can affect their attitude toward patient and might be affecting the possibility of schizophrenia relapse. This study intended to seek the correlation between caregiver s acceptance and quality of life with relapse of schizophrenia outpatient in Surakarta Regional Psychiatric Hospital that involved 35 caregivers with incidental sampling technique. The measurement used on this study are BPRS for assessing schizophrenia relapse (Î± = 0,908), Caregiver Acceptance Scale (Î± = 0,934), and Caregiver Quality of Life Scale (Î± = 0,960). This study used multiple linear regression analysis to analyze the output. Based on the data showed that the level of acceptance and quality of life perceived by caregivers didn t affect the likelihood of relapse of schizophrenia outpatient in Surakarta Regional Psychiatric Hospital.Keywords: Acceptance, Caregiver, Schizophrenia Relapse, Quality of LifeAbstrak. Relapse merupakan keadaan muncul kembali dan bertambah parah simptom yang dialami oleh pasien skizofrenia. Penerimaan dan kualitas hidup dari caregiver dapat mempengaruhi sikapnya dalam merawat pasien sehingga mungkin mempengaruhi kemungkinan terjadinya relapse. Penelitian ini bertujuan untuk mengetahui hubungan antara penerimaan dan kualitas hidup caregiver dengan relapse pada pasien rawat jalan skizofrenia di RSJ Daerah Surakarta yang melibatkan 35 caregiver dengan teknik incidental sampling. Instrumen yang digunakan adalah Skala Relapse Skizofrenia (Î± = 0,908), Skala Penerimaan Caregiver (Î± = 0,934), dan Skala Kualitas Hidup Caregiver (Î± = 0,960). Analisis data dalam penelitian ini menggunakan uji regresi linear berganda. Berdasarkan hasil data penelitian menunjukkan bahwa tingkatan penerimaan dan kualitas hidup dari caregiver tidak memiliki pengaruh terhadap munculnya relapse pada pasien rawat jalan skizofrenia di RSJ Daerah Surakarta.Kata Kunci: Caregiver, Kualitas Hidup, Penerimaan, Relapse Skizofrenia